Grasping intentions: from thought experiments to empirical evidence - Becchio, Cristina; Manera, Valeria; Sartori, Luisa; Cavallo, Andrea; Castiello, Umberto (Frontiers in Human Neuroscience, 2012)
Skepticism has been expressed concerning the possibility to understand others’ intentions by simply observing their movements: Since a number of different intentions may have produced a particular action, motor information – it has been argued - might be sufficient to understand what an agent is doing, but not her remote goal in performing that action. Here we challenge this conclusion by showing that in the absence of contextual information, intentions can be inferred from body movement. Based on recent empirical findings, we shall contend that: i) intentions translate into differential kinematic patterns; ii) observers are especially attuned to kinematic information and can use early differences in visual kinematics to anticipate the intention of an agent in performing a given action; iii) during interacting activities, predictions about the future course of others’ actions tune online action planning; iv) motor activation during action observation subtends a complementary understanding of what the other is doing. These findings demonstrate that intention understanding is deeply rooted in social interaction: by simply observing others’ movements, we might know what they have in mind to do and how we should act in response.